Le financement de l’enseignement supérieur au Québec - Bélanger, Gérard (L'Actualité économique, 1973)
AbstractThe first part of this paper describes the methods by which Quebec universities are financed and stresses the importance of non-accounted expenditures and the relative contribution of the three main sources of financing, namely the federal and provincial governments and the students.The second part investigates the normative aspects of the methods used. Government intervention can be based on three grounds: on the social aspect of the good, on the redistribution objective, and lastly, on the greater indivisibility of university formation costs. It is shown that the present knowledge of the production function and the results on returns to higher education and to university research do not make it possible to determine an optimal amount of resources for this sector.Government intervention in university affairs can take different forms and five principles are formulated as a guide for the establishment of a new financing formula. Finally, the role of student fees is studied as a means to promote efficiency in universities.